2013
DOI: 10.1021/tx400227s
|View full text |Cite
|
Sign up to set email alerts
|

Model Combustion-Generated Particulate Matter Containing Persistent Free Radicals Redox Cycle to Produce Reactive Oxygen Species

Abstract: Particular matter (PM) is emitted during thermal decomposition of waste. During this process, aromatic compounds chemisorb to the surface of metal-oxide-containing PM, forming a surface-stabilized environmentally persistent free radical (EPFR). We hypothesized that EPFR-containing PM redox cycle to produce ROS and that this redox cycle is maintained in biological environments. To test our hypothesis, we incubated model EPFRs with the fluorescent probe dihydrorhodamine (DHR). Marked increases in DHR fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 37 publications
1
68
0
Order By: Relevance
“…7 The critical environmental implication of this work lies in the observation that the clay system, when contaminated, in the absence of any biological components, can form EPFRs at concentrations close to those found in real contaminated soils at ambient temperature, which has wide ranging environmental and human health implications, especially when humidity is relatively low.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…7 The critical environmental implication of this work lies in the observation that the clay system, when contaminated, in the absence of any biological components, can form EPFRs at concentrations close to those found in real contaminated soils at ambient temperature, which has wide ranging environmental and human health implications, especially when humidity is relatively low.…”
Section: Discussionmentioning
confidence: 94%
“…4,5 Organochlorinated contaminants, formed as products and by-products of such remediation processes, are not only toxic in their own right, but the intermediate reactions leading to their formation are also of major concern to environmental safety. 6,7 In particular, these intermediate processes result in the formation of surface-stabilized environmentally persistent free radicals (EPFRs). 2,8,9 Traditionally, EPFRs have been misidentified as molecular pollutants in soils and particulate matter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since DCB230 contains an EPFR that generates hydroxyl radical (OH − ) in biological and other solutions (13, 21), while its synthesis precursors silica and silica CuO do not (13), α-tocopherol was used to determine whether DCB230’s cytotoxicity was radical dependent. Treatment with 25 μg/ml or 100 μg/ml DCB230 significantly reduced HL-1 cell survival during an 8 hour incubation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DCB230 is an environmentally-relevant pollutant particle that produces an electron paramagnetic resonance spectrum indicative of an oxygen centered semi-quinone radical (6, 16). Our group reported that DCB230 produces large numbers of hydroxyl radicals in saline, biological fluids (bronchoalveolar lavage fluid) and cultures of pulmonary epithelial cells (13). Control particles (<200 nm) consisted of Cab-O-sil EH-5 silica beads (Cabot, Alpharetta, Georgia), or CuO-coated (5%) silica beads (CuO/Si; 0.2 μm mean diameter) that do not contain EPFRs.…”
Section: Methodsmentioning
confidence: 99%